Evaluation of Pyrolysis Oil as Carbon Source for Fungal Fermentation - Dörsam, Stefan; Kirchhoff, Jennifer; Bigalke, Michael; Dahmen, Nicolaus; Syldatk, Christoph; Ochsenreither, Katrin (Frontiers in Microbiology, 2016)
Pyrolysis oil, a complex mixture of several organic compounds, produced during flash pyrolysis of organic lignocellulosic material was evaluated for its suitability as alternative carbon source for fungal growth and fermentation processes. Therefore several fungi from all phyla were screened for their tolerance toward pyrolysis oil. Additionally Aspergillus oryzae and Rhizopus delemar, both established organic acid producers, were chosen as model organisms to investigate the suitability of pyrolysis oil as carbon source in fungal production processes. It was observed that A. oryzae tolerates pyrolysis oil concentrations between 1 and 2% depending on growth phase or stationary production phase, respectively. To investigate possible reasons for the low tolerance level, eleven substances from pyrolysis oil including aldehydes, organic acids, small organic compounds and phenolic substances were selected and maximum concentrations still allowing growth and organic acid production were determined. Furthermore, effects of substances to malic acid production were analyzed and compounds were categorized regarding their properties in three groups of toxicity. To validate the results, further tests were also performed with R. delemar. For the first time it could be shown that small amounts of phenolic substances are beneficial for organic acid production and A. oryzae might be able to degrade isoeugenol. Regarding pyrolysis oil toxicity, 2-cyclopenten-1-on was identified as the most toxic compound for filamentous fungi; a substance never described for anti-fungal or any other toxic properties before and possibly responsible for the low fungal tolerance levels toward pyrolysis oil.